2023
DOI: 10.21037/jtd-23-143
|View full text |Cite
|
Sign up to set email alerts
|

PTMA binds to HMGB1 to regulate mitochondrial oxidative phosphorylation and thus affect the malignant progression of esophageal squamous cell carcinoma

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is a malignant tumor of the digestive tract with complex pathogenesis. There is a pressing need to search for ESCC targeted therapy sites and explore its pathogenesis. Prothymosin alpha (PTMA) is abnormally expressed in numerous tumors and has a significant regulatory effect on tumor malignant progression. However, the regulatory role and mechanism of PTMA in ESCC have not yet been reported. Methods: We first detected the PTMA expression in ESCC patients, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It encodes a protein called Prothymosin alpha, which is involved in various cellular processes and has multiple functions within the cell. Prothymosin alpha has been found to interact with High Mobility Group Box 1 (HMGB1), a DNA-binding protein involved in gene regulation, DNA repair, and inflammation [ 40 ]. This interaction is believed to be important for controlling mitochondrial oxidative phosphorylation, which is crucial for cellular energy production.…”
Section: Discussionmentioning
confidence: 99%
“…It encodes a protein called Prothymosin alpha, which is involved in various cellular processes and has multiple functions within the cell. Prothymosin alpha has been found to interact with High Mobility Group Box 1 (HMGB1), a DNA-binding protein involved in gene regulation, DNA repair, and inflammation [ 40 ]. This interaction is believed to be important for controlling mitochondrial oxidative phosphorylation, which is crucial for cellular energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PTMA expression was shown to substantially reduce the activity of ESCC cells while promoting apoptosis. Furthermore, PTMA was found to bind to HMGB1, influencing mitochondrial oxidative phosphorylation and impacting the malignant progression of ESCC ( 54 ). In our present study, we observed overexpression of the PTMA gene in esophageal cancer tissues, which was further validated through in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%